2016
DOI: 10.1177/0886260516670181
|View full text |Cite
|
Sign up to set email alerts
|

A Global Exploratory Analysis of Men Participating in Gender-Based Violence Prevention

Abstract: Organizations addressing gender-based violence (GBV) increasingly include men as partners in prevention efforts. However, little is known about men who get involved in those efforts and what specific actions they take. We present analyses of data from an international sample of men involved in gender-based prevention work that aimed to describe (a) the nature of participants' involvement in prevention efforts, in both formal programming and in their daily lives; (b) characteristics of engaged men, including ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In addition, perhaps the reality that a majority of the events were offered as part of ongoing violence prevention programming (Carlson, Allen, Leek, Storer, Casey, Tolman, 2017) meant that the event was not enough to boost motivation beyond what men come to the events with already. Finally, the men in this sample were already willing to attend a violence prevention programming event, and previous analysis revealed that overall they already had very high levels of gender equitable attitudes (Tolman, Casey, Allen, Carlson, Leek, Storer, 2016). Taken together, the types or classes of events did not clearly inform pathways of motivation.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, perhaps the reality that a majority of the events were offered as part of ongoing violence prevention programming (Carlson, Allen, Leek, Storer, Casey, Tolman, 2017) meant that the event was not enough to boost motivation beyond what men come to the events with already. Finally, the men in this sample were already willing to attend a violence prevention programming event, and previous analysis revealed that overall they already had very high levels of gender equitable attitudes (Tolman, Casey, Allen, Carlson, Leek, Storer, 2016). Taken together, the types or classes of events did not clearly inform pathways of motivation.…”
Section: Discussionmentioning
confidence: 80%
“…Given that the engagement of boys and men is critical to the prevention of SV (Basile et al, 2016;Ricardo & Verani, 2010), research is sorely needed to identify the most effective ways to engage them in these activities. Recent work on engaging men as allies against SV discussed the need to tailor messages to the specific roles men can play in prevention movements, the importance of male opinion leaders, tailored invitations, and connecting the prevention work to community roles that men and boys value (Carlson et al, 2015;Tolman et al, 2016). Furthermore, in a study with men, researchers documented that men's engagement with SV prevention efforts was a process that evolved over time and that it largely happened through existing peer groups, which further supports the potential utility of SNA in identifying male-identified POLs.…”
Section: Discussionmentioning
confidence: 99%
“…As well as the political impacts of activities such as demonstrations and marches, the existence of a tangible movement of men working to end violence women, as can be seen in Spain, can also play an important role in providing support and enabling men to feel a sense that they are 'part of something'; that they are involved in a community of like-minded people rather than being isolated (Tolman et al, 2019).…”
Section: Visible Political Demonstrations With Other Menmentioning
confidence: 99%